Hubungan Dukungan Guru, Ayah, Ibu, dan Teman Sebaya dengan Perilaku Hidup Bersih dan Sehat - Hartini, Sri; Handayani, Lina; Sunardi, Kartika Setyaningsih (Universitas Ahmad Dahlan, 2018)
Background: Helathy life behavior is very important among students to gain good achievment. The research aimed to determine relationships between teachers, fathers, mothers support and peer supports with clean and healthy life behavior among students. Method: This was analytic observational research with cross sectional approach. There were 74 respondents participate din this study. Sample was taken by purposive sampling technique. Chi square test and logistic regression test were employed to analize the data. Results: The factors that establish relations with health and clean life behaviors were teacher’s support (p value 0.047); father’s support (p value 0.002); mother’s support (p value 0.107) and friends support (p value 0.007). Mutivariate test resulted that the most factor that very influential was fathers support. Conclusion: There were relationships between teacher’s support, father’s support, and friend’s support with health and clean life behaviors of students. Father’s support was the most influental factor.